2011
DOI: 10.1093/infdis/jir522
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Mediates Fatal Immunopathology in Mice During Treatment of Secondary Pneumococcal Pneumonia Following Influenza

Abstract: Host inflammatory responses contribute to the significant immunopathology that occurs during treatment of secondary bacterial pneumonia following influenza. We undertook the present study to determine the mechanisms underlying disparate outcomes in a mouse model with β-lactam and macrolide antibiotics. Lysis of superinfecting bacteria by ampicillin caused an extensive influx of neutrophils into the lungs resulting in a consolidative pneumonia, necrotic lung damage, and significant mortality. This was mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 51 publications
3
90
1
Order By: Relevance
“…Interestingly, the “bacterial‐sensing” TLRs (2 and 4) were also reported to be suppressed 27, 28. Downregulation of these TLRs may impair phagocyte recruitment and bacterial elimination, contributing to the risk of secondary infections 9, 30, 31, 32. We found no significant difference in TLR expression pattern or magnitude between A/H3N2 and A/H1N1pdm09 infections, unlike their adaptive immune responses 20.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, the “bacterial‐sensing” TLRs (2 and 4) were also reported to be suppressed 27, 28. Downregulation of these TLRs may impair phagocyte recruitment and bacterial elimination, contributing to the risk of secondary infections 9, 30, 31, 32. We found no significant difference in TLR expression pattern or magnitude between A/H3N2 and A/H1N1pdm09 infections, unlike their adaptive immune responses 20.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, understanding the mechanism by which pneumococcal lysis is regulated is crucial for the development of novel chemotherapeutic strategies. Since pneumococcal lysis by antibiotics could result in the exacerbation of clinical symptoms, the treatment of pneumococcal pneumonia should be undertaken in such a way so as to avoid bacterial lysis [28]. However, the indicator(s) of pneumococcal lysis during infection and sepsis, and the process by which lysis is modulated remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…There is some parallel to bacterial pneumonia after influenza: a state of heightened inflammation, while perhaps helpful for clearing an infection, also causes more tissue damage in the lungs and increases susceptibility to bacterial superinfection. 8 This translational study advances the field and raises more questions: (1) Will the trend toward fewer infectious complications in the hydroxyurea arm of the BABY HUG study of young children with SCD be confirmed in other hydroxyurea clinical trials? Or is this an additional impetus for a registry of hydroxyurea patients?…”
Section: Org Frommentioning
confidence: 99%
“…In 2008, in experiments carried out by investigators in Boston and the Pavia Amyloidosis Research and Treatment Center, amyloid proteins were extracted from fat specimens, separated using two-dimensional polyacrylamide gels, and identified by matrix-assisted laser desorption/ ionization mass spectrometry and peptide mass fingerprinting. 8 In the current report, this technique has been refined to work on easily obtained fat aspirate specimens without the need for electrophoretic separation, and used to accurately identify the amyloid protein in 26 patients. 1 In 2009, Vrana et al reported on the use of laser capture microdissection to isolate deposits from which amyloid fibrils were extracted and subjected to tandem mass spectrometry to identify the amyloid proteins.…”
mentioning
confidence: 99%